(untitled) (Research, Society and Development, 2022)
Objective: indicate the aspects of Burnout in Intensive Care professionals during the COVID-19 pandemic. Methodology: this is an integrative literature review, prepared according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) instructions. The selection and sampling took place through the Virtual Health Library (BVS) and the National Library of Medicine (PubMed) databases and were used to search for the following descriptors: "burnout", "intensive care" and " COVID19. Results and Discussion: 7 studies composed this article and their findings show a high prevalence of Burnout in all dimensions with high risk in Intensive Care Unit (ICU) professionals compared to those who do not work in this department, a worrying situation for the well-being of professional employees in the ICUs with a consequent barrier to patient care and even the strong desire of those professionals to leave the health care area. Final Considerations: The overload and exhaustion in the face of a never experienced pandemic came with the sudden change in most health care professional work and there was a need for greater attention to these professionals, including prevention and attitudes planning that could minimize or eliminate the Burnout in intensive care workers.